1992
DOI: 10.1111/j.1439-0434.1992.tb01227.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Effects on Fungal Leaf Diseases of Wheat in Relation to Epidemiology

Abstract: Wheat plants at growth stages tillering, stem elongation, ear emergence and anthesis were exposed to 80, 160, 240 μg m−3 ozone for 5 days (7 h per day) and to charcoal‐filtered air. Post‐exposure inoculations with Septoria nodorum or Bipolaris sorokiniana revealed a faster growth of lesions on ozonated leaves. However, whereas maximum size of Septoria lesions was measured on leaves exposed to the highest concentration of O3, Bipolaris lesions developed best at 160 μg m−2 and were significantly reduced at 240 μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
(14 reference statements)
4
8
0
Order By: Relevance
“…It is therefore tempting to suggest that ozone exposure prior to infection primed a defence response in the plant, leading to increased basal resistance against B. graminis . However, exposure to ozone concentrations above 100 ppb in wheat reduced powdery mildew disease as observed in this study, whereas concentrations similar to the ones applied here increased disease (von Tiedemann, ). The effect of ozone, therefore, seems to depend on the specific plant–pathogen interaction and the level of ozone exposure, even within closely related biotrophic pathogens.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is therefore tempting to suggest that ozone exposure prior to infection primed a defence response in the plant, leading to increased basal resistance against B. graminis . However, exposure to ozone concentrations above 100 ppb in wheat reduced powdery mildew disease as observed in this study, whereas concentrations similar to the ones applied here increased disease (von Tiedemann, ). The effect of ozone, therefore, seems to depend on the specific plant–pathogen interaction and the level of ozone exposure, even within closely related biotrophic pathogens.…”
Section: Discussionsupporting
confidence: 68%
“…This suggests that basal resistance against the biotrophic B. graminis and hemibiotrophic B. sorokiniana must be different despite the apparent similarities in the early infection process. Exposure to [O 3 ] comparable to the concentrations used here also increased infection with B. sorokiniana in wheat (von Tiedemann, ). However, higher concentrations (above 120 ppb) either had no or a negative effect on infection in B. sorokiniana and D. teres (von Tiedemann, ; Plessl et al ., ).…”
Section: Discussionmentioning
confidence: 66%
“…In the present study enhancement in susceptibility of O 3 predisposed wheat to B. sorokiniana, a hemibiotrophic pathogen was observed. This observation confirms the Tiedemann (1992) reports that susceptibility of wheat to Septoria nodorum and B. sorokiniana after O 3 exposure increased. Mikkelsen et al (2015) also reported increased and decreased infection by the hemibiotrophic spot blotch fungus and biotrophic powdery mildew fungus, respectively, under elevated O 3 , compared to ambient conditions, implying that O 3-induced changes in disease severity could be linked to the trophic lifestyle of the pathogens.…”
Section: Discussionsupporting
confidence: 82%
“…SO 2 has declined more rapidly than the other pollutants (35) and is much better correlated with the Broadbalk pathogen DNA data. It may act alone (36) or in a mixture with other pollutants (37) such as ozone, which is considered to favor infection by necrotrophic pathogens such as P. nodorum (23), presumably by inducing premature senescence of wheat tissues and nutrient leakage. By contrast, the hemibiotrophic M. graminicola, which penetrates leaves through stomata rather than directly through the cuticle and has a longer latent period than P. nodorum (6), might be adversely affected by SO 2 pollution, like other hemibiotrophs (38,39).…”
Section: Correlationsmentioning
confidence: 99%